The Importance Of Authentic Materials In Developing Appropriate And Effective Listening Skills - Fithriyah Fithriyah (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2015)
There has been a growing interest in using authentic materials for the teaching of listening. In order for learners to acquire the target language, teachers need to present the real listening situation of the language. Although authentic materials have positive impact for learners and teachers, they may give difficulties for listeners to catch and understand the text. Thus, some considerations should be taken in order to develop appropriate and effective listening skills.